Performance of Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae) on Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) eggs at laboratory and field conditions - Hosam M. K. H. El-Gepaly; Khaled M. A. Abdelhameed; Shimaa Y. E. Shakl; Ahmed A. Saleh; Elsayed E. Hafez (Scientific Reports)
Abstract The fall armyworm (FAW), Spodoptera frugiperda (Smith), is a significant pest threatening crops like maize across Africa, necessitating sustainable pest management alternatives. This study evaluates the efficacy of Trichogramma evanescens as a biological control agent against FAW egg masses in Egypt under laboratory and semi-field conditions. FAW larvae were initially collected from infested maize fields and reared on castor-oil plant leaves. Meanwhile, T. evanescens was propagated using Sitotroga cerealella eggs as hosts. The host eggs, aged 18 to 24 h, were sterilized with UV light to prevent host development while maintaining suitability for parasitism. Using custom-designed parasitoid incubators and hemisphere clip-cages, experiments focused on various egg mass configurations, assessing the effects of scales and layering. Laboratory conditions were controlled at 25 ± 2ºC and 55 ± 5% relative humidity, while semi-field trials used large cages in maize fields to approximate natural conditions. The results showed that in laboratory settings, parasitism rates averaged 5.96%, 2.00%, and 1.56% for non-, average-, and dense-scale egg masses, respectively. For egg masses with varying layers, parasitism rates were 5.24% for single-layer, 3.09% for double-layer, and 1.18% for ple-layer, regardless of scale presence. In semi-field conditions, parasitism rates were 1.01% for single-layer, 1.13% for double-layer, and 0.59% for triple-layer egg masses. Correspondingly, parasitism rates for non-, average-, and dense-scale eggs were 1.85%, 0.60% and 0.27%. The study concludes that T. evanescens shows promise for integrated pest management programs; however, its effectiveness is constrained by physical and environmental variables. Optimizing the timing of parasitoid releases and selecting robust strains could enhance the effectiveness of biological control, reducing reliance on chemical pesticides in Egypt.